Impact of Inorganic Arsenicals on Vegetative Growth of Two Pakistani Origins Sunflower Cultivars - Muhammad Asif Imran; Feroza Hamid Wattoo; Muhammad Nawaz Chaudhry; Muhammad Hamid Sarwar Wattoo; Khan Rass Masood (Journal of Chemistry)
Inorganic arsenicals impact on vegetative growth of two sunflower (Helianthus annuus L.) cultivars (FH-385 as Hybrid 1 and FH-405 as Hybrid 2) was monitored. Various levels of two different sodium salts of arsenic, namely, sodium arsenate (Na2HAsO4·7H2O) as source of As5+ and sodium arsenite (NaAsO2) as source of As3+, were used to evaluate the effect of arsenic on plant water relation parameters. Significant stress effects were found when arsenic was higher in concentrations (>60 mg/kg soil of both salts) as compared to control plants. Genotype FH-405 showed higher levels for shoot and root length, water contents, number of leaves, and leaf area, which indicates well adaptation of this cultivar in arsenic contaminated environment. T5 (100 mg/kg) of both salts showed notable stressful impacts as compared to low arsenic concentrations (20, 40 mg/kg) and especially control plants in case of all morphophysiological parameters of sunflower cultivars.